Motif Penggunaan Influencer Dalam Iklan Media Sosial Di Sumatera Barat (Studi Kasus Pada Penggunaan Uda Rio Sebagai Influencer Pada Iklan Media Sosial Di Sumatera Barat) - Eriend, Dion; Flowerina, Indria; Ingrid, Tiara Sesilia; Rani, Rani (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
In today's increasingly developing digital and social media era, the role of influencers in social media advertising is becoming increasingly important. Many parties, both individuals, companies and other agencies use the services of influencers in their social media ads. This is inseparable from their ability to influence the opinions and even behavior of their followers, including in the context of purchasing decisions and using services. In West Sumatra itself, there are quite a lot of social media ads that use the services of influencers in social media ads. One of the influencer figures that is used quite often is Verio Hasferi or better known as Uda Rio. Uda Rio is one of the Content Creators who has many followers on his various social media accounts. This study explains how the motive for the use of Influencers in social media advertising in West Sumatra by taking a case study on the use of Uda Rio as an Influencer in social media advertising using the concept approach of the communicator condition theory which includes aspects of credibility, attractiveness and strength. This study uses a descriptive qualitative approach. The determination of informants in this study uses a purposive mechanism by setting informant criteria. The data collection techniques used in this study are in-depth interviews, observations, and documentation. Data analysis in this study uses Miles and Huberman analysis techniques, namely data codification, data presentation, and conclusion / verification. The result of this study is that the motive for using Uda Rio as an influencer in social media advertising in West Sumatra is based on credibility and attractiveness factors. The attraction factor is the main and most dominant consideration used as a reason for choosing influencers.